Pharmacological activation of estrogen receptors-α and -β differentially modulates keratinocyte differentiation with functional impact on wound healing - Peržeľová, Vlasta; Sabol, František; Vasilenko, Tomáš; Novotný, Martin; Kováč, Ivan; Slezák, Martin; Ďurkáč, Ján; Hollý, Martin; Pilátová, Martina; Szabo, Pavol; Varinská, Lenka; Čriepoková, Zuzana; et al. (International journal of molecular medicine, 2016)
Estrogen deprivation is considered responsible for many age-related processes, including poor wound healing. Guided by previous observations that estradiol accelerates re‑epithelialization through estrogen receptor (ER)‑β, in the present study, we examined whether selective ER agonists [4,4',4''-(4-propyl [1H] pyrazole-1,3,5-triyl)‑trisphenol (PPT), ER‑α agonist; 2,3-bis(4-hydroxyphenyl)-propionitrile (DPN), ER‑β agonist] affect the expression of basic proliferation and differentiation markers (Ki‑67, keratin‑10, ‑14 and ‑19, galectin‑1 and Sox‑2) of keratinocytes using HaCaT cells. In parallel, ovariectomized rats were treated daily with an ER modulator, and wound tissue was removed 21 days after wounding and routinely processed for basic histological analysis. Our results revealed that the HaCaT keratinocytes expressed both ER‑α and ‑β, and thus are well-suited for studying the effects of ER agonists on epidermal regeneration. The activation of ER‑α produced a protein expression pattern similar to that observed in the control culture, with a moderate expression of Ki‑67 being observed. However, the activation of ER‑β led to an increase in cell proliferation and keratin‑19 expression, as well as a decrease in galectin‑1 expression. Fittingly, in rat wounds treated with the ER‑β agonist (DPN), epidermal regeneration was accelerated. In the present study, we provide information on the mechanisms through which estrogens affect the expression patterns of selected markers, thus modulating keratinocyte proliferation and differentiation; in addition, we demonstrate that the pharmacological activation of ER-α and -β has a direct impact on wound healing.
Keywords: Cell Line; potkani Sprague-Dawley; alfa receptor estrogenů; buněčná diferenciace; Pyrazoles; beta receptor estrogenů; kůže; fenoly; Keratinocytes; keratinocyty; Animals; lidé; nitrily; Wound Healing; ženské pohlaví; Skin; Humans; zvířata; Estrogen Receptor alpha; Estrogen Receptor beta; buněčné linie; Rats, Sprague-Dawley; Nitriles; Phenols; Female; pyrazoly; Cell Differentiation; hojení ran